CLASSROOM ASSESSMENT: BAGIAN INTEGRAL PROSES PEMBELAJARAN KEJURUAN DALAM UPAYA MENYIAPKAN TENAGA KERJA SECARA HOLISTIK - Wagiran, Wagiran (INVOTEC, 2011)
Assessment of student achievement needs to change, largely because today's students face a world that will demand new knowledge and abilities. In the global economy of the 21st century, students not only need to understand the basics, but also to think critically, to analyze, and to make inferences. In order to develop these skills, changes in assessment at school and classroom level are required. Classroom assessment is an effective strategy to improve the quality of learning to achieve the goals of creating graduates with holistic mastery of cognitive, affective, and psychomotor ability, according to the demands of human resources in the global era.